Diseño de una metodología de auditoría tributaria aplicada al sector editorial. Caso de estudio compañía Santillana S.A., ejercicio fiscal 2012 - Quelal Haro, Luis Miguel (2014)
In recent years, legislation promptly Ecuadorian-tax-area is in constant change, as it is inescapable that the professionals involved in this field, we have a clear picture regarding the key points that need further attention from our management. That is why this proposal fully analyzes the most relevant aspects and shows matrices that help determine the existence of errors, its relevance and possible tax, economic and societal impact of an entity, allowing corporate management to reach a full understanding of their status in meeting obligations with different tax regulators.